A data-driven picking strategy for micro fulfilment centers in quick commerce: the case of Korea - Kim, Kwang-Tae; Son, Dong-Hoon; Kim, Hyunwoo; Lee, Hongchul (Transport, 2026)
Quick Commerce (Q-Commerce) allows customers to receive their orders from near Micro Fulfilment Centers (MFCs) in a short time. However, the fulfilment centers are difficult to maintain responsive and reliable delivery services with traditional Single Order Picking (SOP) systems. Motivated by the above challenge, this study develops a hybrid picking method for an order fulfilment center of a Korean delivery company. The hybrid method considers certain rules for order batching to complement a SOP method. The order batching rules enable pickers to deal with 2 customer orders within a specific range of order lines. The order picking development are based on the results of a Warehouse Activity Profiling (WAP) analysis. This analysis shows possible approaches for the development of the hybrid method by considering arrival rates of customer orders and their variability in terms of item type and quantity. Afterwards, the hybrid method is validated with an agent-based simulation model using actual order information of the case study company. This study finds that the hybrid method shows consistent performance in terms of order picking and fulfilment times under wide ranges of order arrival rate and variability.